جدلية الحرية والموت في شعر خليل حاوي - جابر يوسف حامد (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
تتناول هذه الدراسة موقف " خليل حاوي " من موضوعي الحرية والموت بوصفهما من أهم الموضوعات التي ترتبط بوجود الإنسان وقضاياه الكبرى . وتقوم بتسليط الضوء على تجليات هذين الموضوعين في شعره ، مستهدفة الكشف عن عالم الشاعر الداخلي ، ومحاولة القبض على خصوصية تجربته الشعرية التي جسّدت أزمته الشخصية ومأزقه الوجودي ، دون أن ننسى المقومات الموضوعية التي أسهمت في تشكيل وعيه الحضاري وبناء شخصيته الإنسانية . This study deals with Khalil Hawi’s attitude towards death and freedom – the two issues most inherently linked to man’s existence and man’s primordial, primeval concerns . It sheds light on the poetic mediation of these two issues is the whole walk of Haw’s poetry, seeking to reveal the poet’s inner world and systematically trying to capture the specific peculiarity of his poetic experience . Hawi’s personal and existential crisis, this study claims, is embedded in his poetic experience, meshed with the other objective Factors which helped Formulate his human character and his cultural consciousness .